ANALISIS NETNOGRAFI SENTIMEN PENGGUNA TWITTER TERHADAP PEMBUKAAN KEMBALI PARIWISATA DI TENGAH PANDEMI COVID-19 - Aditya Rizki Rinaldi; Dyah Mutiarin; Janianton Damanik3 (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2021)
The government is required to be alert in following up on the spread of Covid-19, on the other hand the government is asked to stabilize the community's economy, so that the government reopens access and the tourism industry. Public opinion can be formed easily through sentiments expressed online (in the network), so that to anticipate this can be done through exploration of social media content. This research was conducted by exploring public sentiment, especially citizens regarding the policy of reopening tourism in Indonesia in the midst of the Covid-19 pandemic, to explore public opinion in Indonesia. A qualitative approach is used in this study with netnographic analysis to analyze warganet posts or writings on Twitter social media. Twitter social media data collection is taken using the help of the Google Chrome platform, namely NCapture, and the data is managed using NVivo 14 software as a qualitative research management tool. NCapture found 513 posts filtering the word “new travel”. The results of the study on 297 posts showed a neutral or impartial attitude from Twitter users. Based on the results of this analysis, there are findings that show sources of Twitter content with negative or positive sentiments, where government accounts are known not to be the source of posts with negative sentiments. The findings of netizen sentiment on Twitter can be a direction in finding out people's attitudes and responses to policies in reopening tourism in the midst of the Covid-19 pandemic. The results of the analysis show that most netizens provide neutral sentiment regarding the reopening of tourism or are in an impartial position. This study also pointed out some of the words and phrases that often appear such as "travel", "open" and "health protocol". Interestingly, the findings of this study show that among Twitter accounts there are only government accounts that do not have negative sentiments in the tweets they make.